Techniques and Institutions The Transformation of British Dance Tradition through South Asian Dance - Prickett, Stacey (Edinburgh: Edinburgh University Press, 2004)
RESUMEN: In 1998, the Imperial Society of Teachers of Dancing (ISTD) created a South Asian Dance Faculty, expanding its range of dance styles for examination. The added imports of Bharatanatyam and Kathak are classical Indian dance forms which have transformed the face of British dance despite their relatively short history here. Inclusion of the new forms was initiated by Akademi, a British South Asian dance organization, with funding from the Arts Council of England. Delving beyond ISTD's response to the increasing multi-cultural face of British society, the organisation's expansion opens avenues of inquiry into the relationship between dance techniques and British institutions. Fundamental dichotomies arise in considering identity and tradition in relation to the location and function of South Asian dance in Britain. How does the addition of South Asian dance fit into the stated mission of the ISTD? And how does the ISTD fit into the South Asian dance community and the larger context of a mainstream arts communities? Other relevant issues concern the extent to which classical South Asian dance forms are culturally specific and their modification to fit within an ISTD curriculum. Questions on the location and function of the art forms exist within broader fundamental debates centring on the definition of the term "British" -whose version of identity is invoked by the name? And while definitive answers are still elusive, issues of agency arise in considering the transformation of British dance. Interviews with members of the ISTD South Asian Dance Faculty and research collected in the Leverhulme Trust South Asian Dance in Britain project are drawn on to examine the impact of South Asian dance on a British dance identity.